Implementation of integrated care for type 2 diabetes Mellitus and Periodontitis in Germany: study protocol for a practice-based and cluster-randomized trial - Patrick Hennrich; Annika Queder; Attila Altiner; Sinclair Awounvo; Jan Dyczmons; Julian Eigendorf; Stella Erdmann; Thomas Grobe; Andreas Gutscher; Nicole Herzig; Søren Jepsen; Nadja Kairies-Schwarz; et al. (BMC, 2024)
Abstract Background Type 2 Diabetes mellitus (T2DM) and periodontitis share common risk factors and influence one another. However, primary care and oral health care continue to operate separate from each other and fail to synchronize care for patients with T2DM and periodontitis. The purpose of this practice-based trial is to evaluate the implementation of a new integrated care pathway for patients with T2DM and periodontitis. The new approach integrates a screening for T2DM risk in dental care settings in patients with periodontitis, a screening for periodontitis risk in primary care settings in patients with T2DM, and mutual referrals between dentists and primary care physicians. Methods Two practice-based studies will be carried out in parallel: (i) In dental care settings: a practice-based, multi-centric, cluster-randomized, controlled trial with a control and an intervention group; (ii) in primary care settings: a practice-based, multi-centric, non-randomized, controlled trial with a synthetic control group calculated from claims data. Following a two-step recruitment approach, 166 dentists and 248 general practitioners will be recruited, who themselves will recruit a total of 3808 patients in their practices. Patient data will be collected at baseline, 12 months, and 24 months after study enrollment. The evaluation comprises: (i) impact evaluation, using a hierarchical linear mixed model; (ii) process evaluation, based on surveys alongside the trials; (iii) economic evaluation. In addition, a Discrete-Choice-Experiment will identify provider's payment preferences for the new care approach. Discussion Upon successful implementation, the intervention will enable health care providers to detect a risk for T2DM and periodontitis in patients at an early stage, thus providing patients an opportunity for timely diagnosis and therapy. Ultimately, this can lead to increased quality of life and reduced health care expenditures. On a methodologic level, the project provides novel insights into a complex intervention on the intersection of general practice and dental care. Trial registration The study was prospectively registered at the German Clinical Trials Register ( https://drks.de/search/de/trial/DRKS00030587 ) on 3. July 2023 under ID "DRKS00030587".